USP10 stabilizes BAZ1A to drive tumor stemness via an epigenetic mechanism in head and neck squamous cell carcinoma - Yanni Shi; Jiawei Ding; Xiao Ling; Danfeng Xu; Yan Shen; Xingjun Qin (Cell Death and Disease)
Abstract Aberrant epigenetic remodeling events occurred in head and neck squamous cell carcinoma (HNSCC) contribute to tumor stemness and chemotherapy resistance, yet little is known. In this study, we identified that ubiquitin-specific peptidase 10 (USP10) is up-regulated in HNSCC tissues, and high USP10 is associated with poor prognosis of patients. Functionally, USP10 serving as an oncogene potentiates the proliferation and metastasis of HNSCC cells in vitro and in vivo. Mechanistically, USP10 physically interacts with, deubiquitinate, and stabilizes BAZ1A proteins. In addition, BAZ1A complexes with SOX2 to drive the enhancer-promoter interaction and facilitate the recruitment of BRD4, thereby activating the expressions of cancer stem cells (CSCs)-related signature. Therefore, we found that USP10 relied on BAZ1A to enhance HNSCC stemness, progression, and chemotherapy resistance. The pharmacology research implicated that BAZ1A-IN-1, one specific BAZ1A inhibitor, could effectively inhibit HNSCC stemness, distal metastasis, and cisplatin resistance. Together, our study revealed a novel USP10/BAZ1A/stemness axis and one significant therapeutic target for USP10-driven HNSCC.